Analisis Faktor-Faktor yang Mempengaruhi Kinerja Karyawan - Abdul Latief; Koko Pribadi; Mummah Rizqi Zati (Universitas Negeri Medan, 2018)
This study aims to determine the effect of occupational safety and health on employee performance. The sample in this study amounted to 86 respondents. The data used are primary data analyzed using multiple linear regression equations, hypothesis testing (t test and F test) and the coefficient of determination (R2). The results of the study obtained Y = 2,247 + 0,443X1 + 0,445X2. Constants of 2,247 were performance before being influenced by occupational safety and health variables. The regression coefficient is 0.443X1, indicating that work safety has a positive effect on performance. The regression coefficient is 0.445X2, indicating that occupational health has a positive effect on performance. The result of the safety t test is tcount> ttable (2.086> 1.988), it can be stated that statistically the safety variable has a significant effect on performance. The results of the health t test tcount> t table (2.106> 1.988), it can be stated that statistically the health variables have a significant effect on performance. F test results, Fcount> Ftable (62,043> 3,11), it can be stated statistically the variables of occupational health and safety have a significant effect on performance. The test results of the coefficient of determination (R2) of 0.599 or 59.9% of the variables of occupational health and safety affect employee performance and the remaining 40.1% is influenced by other variables not examined.